2019
DOI: 10.1039/c9ra05793e
|View full text |Cite
|
Sign up to set email alerts
|

Removal of methylene blue dye by solvothermally reduced graphene oxide: a metal-free adsorption and photodegradation method

Abstract: A metal-free MB dye removal process was carried out by solvothermally synthesized rGO. After optimization, near-complete dye removal was achieved via an adsorption and UV photodegradation route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 63 publications
3
21
0
Order By: Relevance
“…At 80 • C, the peak was observed at 24.26 • with interlayer d-spacing of 0.367 nm, while the diffraction peak at 12.04 • [30] was unobservable, indicating the completion of GO reduction. This interlayer spacing of rGO, identical to those of previously reported rGO and close to that of graphite, indicates the efficient removal of oxygen functionalities of GO by reduction [6,30,54]. However, the shape of the characteristic diffraction of rGO produced in this work is broader than the previously reported lemon-juice-based rGO, showing both shape and broad peaks [46].…”
Section: Characterizationsupporting
confidence: 87%
See 1 more Smart Citation
“…At 80 • C, the peak was observed at 24.26 • with interlayer d-spacing of 0.367 nm, while the diffraction peak at 12.04 • [30] was unobservable, indicating the completion of GO reduction. This interlayer spacing of rGO, identical to those of previously reported rGO and close to that of graphite, indicates the efficient removal of oxygen functionalities of GO by reduction [6,30,54]. However, the shape of the characteristic diffraction of rGO produced in this work is broader than the previously reported lemon-juice-based rGO, showing both shape and broad peaks [46].…”
Section: Characterizationsupporting
confidence: 87%
“…Under highly acidic conditions, the basic moieties in MB (pKa = 2.6) accept protons to make MB di-cationic, and the high polarity of MB results in low affinity with the hydrophobic rGO surface, leading to very low removal efficiency. As the pH gets higher, MB becomes stably mono-cationic with a moderate amphiphilicity, and the adsorption becomes preferable to enhance the removal efficiency [54,67,68]. It is reported that the decrease in the cationic nature of MB in basic media increasingly facilitates its adsorption [54,69].…”
Section: Effect Of Phmentioning
confidence: 99%
“…GO was produced according to our previous work. 22 Then, 200 mg of synthesized GO powder was suspended in a solvent of 2 : 1 (volume) ethanol/deionized water mixture. The suspension was sonicated in ultrasonic bath for 30 min to produce a stable dispersion.…”
Section: Preparation Of Rgomentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] In addition, our earlier work had shown that rGO synthesized via facile solvothermal method can completely photodegrade MB dye under UV illumination aer process optimizations. 22 However, there are some contradicting past reports on the origin of photoactivity of GO and rGO for dye photodegradation. For instance, Guardia et al stated that GO under UV illumination degraded RhB via photoinduced heating of localized GO sheets and not photocatalytic degradation.…”
Section: Introductionmentioning
confidence: 98%
“…Silica is reported to be a good sorbent of dye. Up to 80% removal of the methylene blue was reported by Enrique C. Peres et al [24]. The performance of graphene oxide nanoparticles in the removal of dye is better than the silica nanoparticles.…”
Section: Dye Absorption Studiesmentioning
confidence: 93%